Formy czasowników w didaskaliach "Wyzwolenia" Stanisława Wyspiańskiego jako próba przełamania konwencji = Verb forms in the stage directions in Stanisław Wyspiański`s "Wyzwolenie" ("Liberation") as an attempt to break with the conventions - Woźniak-Wrzesińska, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the introduction to the paper analyzing the stage directions in "Liberation" written by S. Wyspiański the author presents the present state of the research concerning the stage instructions. She begins the discussion with characteristics of the research tools applied by the interpreters who have attempted to analyze the text to date, and then moves on to the analytical part.
Keywords: Wyspiański, Stanisław (1869-1907); didaskalia; tekst poboczny; stylistyczna akomodacja; funkcje czasu; stage directions; stage instructions; blocking; stylistic accommodation; tense functions